2017
DOI: 10.1587/elex.14.20170230
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics for series and parallel circuits of flux-controlled memristors

Abstract: With the closed principle of flux-controlled memristors, the parallel, series, and array circuits of flux-controlled memristors are made discussed. The parameters for equivalent flux-controlled memristors of these memristor systems are deduced theoretically. The mathematical relationships between the parameters of equivalent flux-controlled memristors and those of corresponding component memristors are attained. The results are interesting for the application of serie, parallel, and array circuits of flux-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is demonstrated that the memristor series‐parallel circuits allow for high data density, better performance, and better dynamic characteristics. In 2017, He and Huang used a third‐order smooth flux‐controlled memristor model to theoretically analyse the equivalent resistance of series‐parallel and reverse series‐parallel circuits, and conducted numerical simulations [17]. In 2018, Zheng studied the memristor series‐parallel circuit with a coupling effect and applied it to the classic Chua's circuit to generate a chaotic attractor [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the memristor series‐parallel circuits allow for high data density, better performance, and better dynamic characteristics. In 2017, He and Huang used a third‐order smooth flux‐controlled memristor model to theoretically analyse the equivalent resistance of series‐parallel and reverse series‐parallel circuits, and conducted numerical simulations [17]. In 2018, Zheng studied the memristor series‐parallel circuit with a coupling effect and applied it to the classic Chua's circuit to generate a chaotic attractor [18].…”
Section: Introductionmentioning
confidence: 99%